Genetic Influences on Hippocampal Subfields: An Emerging Area of Neuroscience Research. (June 2021) - Vilor-Tejedor, Natalia; Evans, Tavia E.; Adams, Hieab H.; González-de-Echávarri, José María; Molinuevo, José Luis; Guigo, Roderic; Gispert, Juan Domingo; Operto, Grégory
Abstract : There is clear evidence that hippocampal subfield volumes have partly distinct genetic determinants associated with specific biological processes. The identification of genetic correlates of hippocampal subfield volumes may help to elucidate the mechanisms of neurologic diseases, as well as aging and neurodegenerative processes. However, despite the emerging interest in this area of research, the current knowledge of the genetic architecture of hippocampal subfields has not yet been consolidated. We aimed to provide a review of the current evidence from genetic studies of hippocampal subfields, highlighting current priorities and upcoming challenges. The limited number of studies investigating the influential genetic effects on hippocampal subfields, a lack of replicated results and longitudinal designs, and modest sample sizes combined with insufficient standardization of protocols are identified as the most pressing challenges in this emerging area of research.